Antibiotics removal from aquaculture effluents by ozonation: chemical and toxicity descriptors. (30th June 2022) - Gorito, Ana M.; Ribeiro, Ana R. Lado; Rodrigues, Pedro; Pereira, M. Fernando R.; Guimarães, Laura; Almeida, C. Marisa R.; Silva, Adrián M.T.
Highlights: Ozonation investigated for the removal of antibiotics from aquaculture effluents. Oxytetracycline, sulfamethoxazole and trimethoprim attacked by O3 directly. Florfenicol removed by hydroxyl radicals (HO ) only. Sulfadimethoxine degradation is significantly affected by the water matrix. Toxicological evaluation did not show increase of water toxicity after ozonation. Abstract: Antibiotics are often applied in aquaculture to prevent fish diseases. These substances can cause disturbances on receiving waters, when not properly eliminated from the aquaculture effluents. In this work, ozone (O3 ) was investigated as a possible oxidizing agent to remove fishery antibiotics from aquaculture effluents: florfenicol (FF), oxytetracycline (OTC), sulfadimethoxine (SDM), sulfamethoxazole (SMX), and trimethoprim (TMP). Batch experiments were performed using ultrapure water and aquaculture effluents spiked with a mixture of target antibiotics at relatively high concentrations (10 mg L -1 each). OTC, SMX and TMP were fully removed (< 30 min) regardless of the tested conditions, mainly by O3 direct attack. In contrast, FF was partially removed in 30 min (∼ 10 and 60%, in aquaculture effluents and ultrapure water, respectively), but only in the presence of hydroxyl radicals (HO ), the FF concentrations reaching levels below the detection limits in ultrapure water after 60 min. In the case of SDM, its degradation was highly influenced by the selected water matrix, but with removals always higher than 68%. In continuous-flow experiments applying more environmentally relevant antibiotic concentrations (100 ng L -1 each) and low O3 doses (1.5 mg L − 1 ), ozonation highly removed (> 98%) all tested antibiotics from aquaculture effluents with a hydraulic retention time (HRT) of 10 min, except FF (68%). Although by-products were detected in treated samples, zebrafish ( Danio rerio ) embryotoxicity tests did not show a toxicity increase by applying this ozonation treatment. Ozonation is thus a possible solution to remove antibiotics from aquaculture effluents. Still, full-scale studies in aquaculture farms are needed, and generation of HO may be favoured to readily oxidize the FF antibiotic. Graphical Abstract: Image, graphical abstract